Depositional, diagenetic and sequence stratigraphic controls on the reservoir potential of the Cretaceous Chichali and Lumshiwal formations, Nizampur Basin, Pakistan - Hashmi, Syed Irfanullah; Jan, Irfan U.; Khan, Suleman; Ali, Nowrad (Journal of Himalayan Earth Sciences, 2018)
The Early to Middle Cretaceous Chichali and overlying Lumshiwal formations from the Nizampur Basin, Pakistan have been investigated to link the reservoir quality with stratal deposition, diagenetic modifications and sequence stratigraphy. The Chichali Formation revealed laterite, glauconitic sandstone and carbonaceous green shale lithofacies, representing middle to outer ramp depositional setting. The presence of bioclastic sandy limestone, quartz arenite and glauconitic sandstone lithofacies within the overlying Lumshiwal Formation represented an inter-tidal to inner ramp depositional setting. The calcite, hematite, smectite, ferroan dolomite and glauconite occurred as cement in the coarse grained facies of the Chichali Formation, thereby reducing porosity, however, grain fracture porosity, and dolomitization, intergranular and dissolution porosity resulted in porosity increase. The overlying Lumshiwal Formation showed both physical, and chemical compaction, authigenic mineralization, cementation and late-stage dissolution. The dominant cement types in the Lumshiwal Formation are calcite, ferroan dolomite, smectite, illite and quartz-overgrowth cements. The primary intergranular porosity, and late-stage diagenetic dissolution- and dolomitization-induced secondary porosity added to the reservoir quality of the Lumshiwal Formation. The sequence stratigraphic analysis revealed that Chichali Formation is deposited during transgressive system tract of 2nd order depositional cycle. The transgression-associated glauconitic sandstone facies of the Chichali Formation acts as a good reservoir, which is bounded by carbonaceous green shale associated with maximum flooding surface. The Lumshiwal Formation is deposited in the regressive 2nd order cycle and is represented by delta plain facies. The quartz arenites represent excellent reservoir potential in the Lumshiwal Formation.